A Smartphone Camera Colorimetric Assay of Acetylcholinesterase and Butyrylcholinesterase Activity - Pohanka, Miroslav; Zakova, Jitka (Sensors (Basel, Switzerland), 2021)
Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) can serve as biochemical markers of various pathologies like liver disfunction and poisonings by nerve agents. Ellman's assay is the standard spectrophotometric method to measure cholinesterase activity in clinical laboratories. The authors present a new colorimetric test to assess AChE and BChE activity in biological samples using chromogenic reagents, treated 3D-printed measuring pads and a smartphone camera as a signal detector. Multiwell pads treated with reagent substrates 2,6-dichlorophenolindophenyl acetate, indoxylacetate, ethoxyresorufin and methoxyresorufin were prepared and tested for AChE and BChE. In the experiments, 3D-printed pads containing indoxylacetate as a chromogenic substrate were optimal for analytical purposes. The best results were achieved using the red (R) channel, where the limit of detection was 4.05 µkat/mL for BChE and 4.38 µkat/mL for AChE using a 40 µL sample and a 60 min assay. The major advantage of this method is its overall simplicity, as samples are applied directly without any specific treatment or added reagents. The assay was also validated to the standard Ellman's assay using human plasma samples. In conclusion, this smartphone camera-based colorimetric assay appears to have practical applicability and to be a suitable method for point-of-care testing because it does not require specific manipulation, additional education of staff or use of sophisticated analytical instruments.
Keywords: kolorimetrie; Ellman’s assay; Humans; Spectrophotometry; point-of-care; cholinesterase; lidé; liver function test; cholinesterasové inhibitory; image analysis; butyrylcholinesterasa; Acetylcholinesterase; Smartphone; organophosphate; Colorimetry; spektrofotometrie; Butyrylcholinesterase; chytrý telefon; acetylcholinesterasa; Cholinesterase Inhibitors; inhibition; Carbamate; diagnosis